Perjuangan Kesetaraan Gender dan Diskriminasi Tokoh Wanita dalam Novel Entrok - Nina Queena Hadi Putri; Hasrul Rahman; Hesti Mutmainah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2018)
This study aims to describe the struggle for gender equality carried out by female character in Okky Madasari's novel entitle Entrok using the study of literary feminism. This research is a qualitative descriptive study with content analysis method which aims to determine the content and meaning contained in the data analyzed. The activities carried out were reading, observing, interpreting, and analyzing Okky Madasari's Entrok. The data sources in this study is Okky Madasari’s novel entitle and relevant literature. The data is gained by reading, taking note, and literature review. The results of this study can be concluded that there is gender equality and discrimination towards female character in the novel Entrok.